Managing organizational change: it’s not just a picnic - Hassan, Arif; Velayutham, Thivagar (University of South Australia, 2006)
The case illustrates several organizational behavior issues such as supervisory behavior and organizational culture, organizational change process and resistance to the change, employees’empowerment and the difficulties involved in introducing Self Managed Team (SMT) concept in the workplace etc. It also highlights the importance of cultural issues in management and in particular the need for top management to understand the culture and values of employees. The case is about a palm oil company in Malaysia where a new CEO takes over and tries to introduce new technology and culture without careful analysis of the situation. The company was earlier run by officers mostly from the army background. The new CEO introduces several changes including employees’ empowerment and self managed work teams demanding supervisors to change their role relationships. This did not work well and in the process an ugly confrontation took place one day between the new CEO and a supervisor, Mr. Ang, who enjoyed tremendous respect from the employees. The supervisor was fired for gross insubordination. However, things did not improve after the departure of Mr. Ang and the CEO wondered why?